1986
DOI: 10.1002/cite.330580602
|View full text |Cite
|
Sign up to set email alerts
|

Koaleszenzprobleme in chemischen Prozessen

Abstract: Das Trennen von Flussig/Flussig-Dispersionen gilt als Verfahrensschritt, der in vielen Fallen im technischen MaBstab erhebliche Schwierigkeiten bereitet. An einer Reihe von Beispielen aus chemischen Prozessen wird gezeigt, wo Phasentrennprobleme auftreten, welche Auswirkungen sie haben und welche industriell praktikablen Methoden fur ihre Losung zur Verfiigung stehen. Die vorgestellte Problemanalyse geht vom Entstehungsmechanismus der Dispersion aus und fuhrt zu einer qualitativen Charakterisierung der verschi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Thus, a novel simple continuous extraction apparatus was developed in this study according to the principle of inclined plate settler (Figure ). A stream of biphasic reaction mixture was fed into the oil–water separator. Due to the density difference between organic layer and aqueous solution, an obvious interface of organic layer and aqueous solution was observed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, a novel simple continuous extraction apparatus was developed in this study according to the principle of inclined plate settler (Figure ). A stream of biphasic reaction mixture was fed into the oil–water separator. Due to the density difference between organic layer and aqueous solution, an obvious interface of organic layer and aqueous solution was observed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In previous work it has been shown that a very strong test for constant system purity is a settling experiment 17, 24. Thus, to generate reproducible data, settling experiments with deionized water and isododecane have been carried out in a washing bottle with a diameter of 50 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The problem of efficient removal of dispersed droplets from gas or vapor stream is important and extensive in many industrial processes. One of the many proposed different improvements of phase separation (Berger, 1986), the application of an electric field seems to be the most promising. Fundamentally, the strong electric fields induce a dipole in the aerosol particles.…”
Section: Electrocoalescencementioning
confidence: 99%